Ideas, Ideology, and the Roots of the Islamic State. Issue 1 (2nd January 2019) - Fadel, Mohammad
ABSTRACT: The ideals that gave rise to Daesh are not so much those of pre-modern Sunni Islam, including Salafism, as they are the ideals that post-colonial Arab states have propagated since the collapse of the Ottoman Empire. In contravention to long-established ideals of Islamic law, post-colonial Arab states have attempted to legitimate their own despotisms through a formal commitment to a certain kind of Islamic normativity. Inasmuch as Islam provides a ready political discourse to resist despotism, it is unsurprising that pan-Arab "Islamist" movements have made resistance to despotism their central concern. Daesh, however, rejects the anti-despotic politics of modern pan-Arab and "Islamist" political movements and instead offers a despotic and apocalyptic religious conception of the political that is as far from the Sunni mainstream as the political despotisms of the post-colonial Arab states. In this respect, there is a deep synergy between Daesh and the despotisms of the modern Arab state, both of which portray themselves as the only alternative to the murderous tyranny of the other. The only long-term solution to Daesh, therefore, is reform of the despotisms of the post-colonial Arab states.